PERBANDINGAN LOYALITAS KONSUMEN DAN STRATEGI PEMASARAN ANTARA ILLOCAKE DAN ROCASTE DI KOTA BIMA - Nandha Ramdani; Muhajirin Muhajirin (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2022)
This study aims to determine the differences in consumer loyalty and marketing strategies between Illocake and Rocaste in Bima City. This research is a comparative study that uses quantitative data from primary data sources. The research instrument used a Likert scale questionnaire. The population used in this research is all Illocake and Rocaste consumers in Bima City in Bima City whose numbers are not known for certain (Unknown Population). The sample in this study were 60 respondents. The sampling technique in this study was carried out by accidental sampling, data collection techniques using observation, questionnaires and library studies with data analysis techniques using validity tests, reliability tests and different tests. The results showed that there was no difference in consumer loyalty but in the marketing strategy between Illocake and Rocaste there was a difference. Keywords : Consumer Loyalty, Marketing Strategies